Combination therapy with prednisone and cyclophosphamide in a 14-year-old boy with pemphigus foliaceus - a case report - Magdalena Salińska; Kamil Trambowicz; Joanna Narbutt; Anna Woźniacka; Aleksandra Lesiak (Termedia Publishing House, 2017)
Introduction . Pemphigus foliaceus is a dermatosis rarely occurring in the paediatric population. Objective. To draw attention to diagnostic and therapeutic difficulties associated with pemphigus foliaceus. Case report. A 14-year-old boy was admitted to our department with seborrhoeic crusts over the anterior and posterior surfaces of the chest and erythematous-infiltrative lesions in the axillary and popliteal fossae. Since histopathological examination revealed features of Darier's disease, acitretin treatment was initiated. No improvement was noted after 3 months. Another skin biopsy was obtained and immunologic tests were carried out. Based on the clinical manifestations and results of additional tests, juvenile pemphigus foliaceus was diagnosed. Prednisone therapy was initiated, however it failed to produce satisfactory improvement in skin lesions. Cyclophosphamide was added to prednisone, causing remission of the disease. Conclusions. In patients with non-characteristic lesions who fail to respond to treatment it is advisable to extend diagnostics by immunologic tests. In the reported case combination therapy with prednisone and cyclophosphamide led to long-term remission, causing no adverse effects.